Contribuição para projeto de terças alveolares protendidas sem armadura transversal - Carvalho, Geovana Izabel de Macedo (2024)
Upon sectioning a hollow core slab into two ribs, a structural element with an innovative manufacturing process is obtained, here referred to as hollow core purlins, proposing a solution for roof structures. Although it offers a potential increase in production for manufacturers of precast concrete elements, hollow core purlins lack regulatory prescriptions, as they do not include transverse reinforcement. Therefore, the objective of the study is to conduct an experimental program to verify the technical feasibility of the structural element and to propose a calculation procedure that reproduces the behavior of the piece. To achieve this goal, six samples of hollow core purlins were studied. Initially, visual analyses were conducted on the manufacturing characteristics and variations in the cross-sectional geometry of each purlin unit. Subsequently, the pieces underwent a non-destructive positive bending strength test to characterize the stiffness and effective tensile strength values of the concrete. Following this, tests were performed to determine the resistance to shear force in order to identify the rupture mechanism of the elements. Finally, the experimentally obtained values were compared to theoretical calculation values based on the concrete compression strength, derived from factory quality control, to establish a relationship that demonstrates the tension shear mechanism, as published by the Brazilian Association of Technical Standards in NBR 14861 (2022), as the calculation procedure that best represents the behavior of the pieces by reproducing considerations about the cross-sectional geometry. The tests conducted in this study demonstrated that the pieces are capable of resisting shear forces, which are considered the main concern in the structural analysis of the element and ensure structural performance in accordance with established regulatory standards, thus ensuring the technical feasibility of hollow core purlins.